2005
DOI: 10.3171/spi.2005.3.5.0364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pilot hole preparation technique on pedicle screw fixation in different regions of the osteoporotic thoracic and lumbar spine

Abstract: Object. The authors evaluated the effects of pilot hole preparation technique on insertional torque and axial pullout resistance in osteoporotic thoracic and lumbar vertebrae. Methods. Using a probe technique and fluoroscopy, 102 pedicle screws were placed in 51 dual-energy x-ray absorptiometry—proven osteoporotic thoracic and lumbar levels. Screws were inserted using the same-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
24

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 32 publications
2
57
0
24
Order By: Relevance
“…Despite technological advances, implant failures, such as screw bending, breakage, and loosening still occur [2,10,40]. It is well established in the literature that the holding power of the pedicle screw is influenced by bone mineral density [5], geometry of the screw [1,20,[25][26][27] and the screw insertion technique employed by the surgeon [5,14,33,38]. It has been reported that the holding power of the pedicle screw is significantly influenced by the size and technique of the pilot hole [5,7,14,15,33].…”
Section: Introductionmentioning
confidence: 99%
“…Despite technological advances, implant failures, such as screw bending, breakage, and loosening still occur [2,10,40]. It is well established in the literature that the holding power of the pedicle screw is influenced by bone mineral density [5], geometry of the screw [1,20,[25][26][27] and the screw insertion technique employed by the surgeon [5,14,33,38]. It has been reported that the holding power of the pedicle screw is significantly influenced by the size and technique of the pilot hole [5,7,14,15,33].…”
Section: Introductionmentioning
confidence: 99%
“…to, no âmbito da cirurgia da coluna vertebral tem sido demonstrado que o macheamento do orifício piloto não aumenta a resistência ao arrancamento dos parafusos (2) e que poderia reduzir essa resistência nos ossos esponjosos e na coluna lombar (6,7) , sem alterar essa propriedade nos parafusos inseridos na coluna torácica (4) .…”
Section: Resultsunclassified
“…Due to the demographic development and the increasing average age of the population, treatment of these conditions often involves instrumentation of osteoporotic spinal segments and the indications for placing instrumentation in patients with osteoporosis will likely continue to broaden [11]. Cancellous bone is more affected by osteoporosis than cortical bone, and it is not surprising that pedicle screw fixation is significantly less effective in patients with low bone mineral density, as its anchorage relies also on the properties of the cancellous bone within the vertebral body [12].…”
Section: Introductionmentioning
confidence: 99%